Integrating ZigBee modem into android platform - Abd Rahman, Akmal Nurhananie; Habaebi, Mohamed Hadi; Ahmed, Musse Mohamud; Khan, Sheroz; Ismail, Mahamod (2014)
This paper integrates ZigBee technology, which falls under IEEE 802.15.4 standard, into the mobile peer-to-peer (P2P) environment. This involves devices with Android 4.0 (Ice Cream Sandwich), which is the lowest version of the Android platform that can be found among mobile devices. Preliminary results has shown that file sharing is possible to work on ZigBee radios, with the time taken for complete transfer depends on the size of the file being shared.